Alterations of Bone Metabolism in Patients with Diabetes Mellitus - Sain S. Safarova (International Journal of Endocrinology)
Aim. The study aims to develop a practical model for screening bone turnover state in patients with diabetes and evaluate its clinical usefulness to identify diabetic osteopathy. Materials. The study was conducted in 2015–2017 in the Endocrinology Department of the Therapeutic Clinic of AM University. A total of 235 patients were assessed in the study (98 with T1DM and 137 with T2DM). 89 nondiabetic subjects served as controls. Bone mineral density (BMD) [by dual energy X-ray absorptiometry (DXA)] and serum markers of bone remodeling [aminoterminal propeptide of procollagen type I (P1NP) and c-terminal telopeptide of type I collagen (CTX)], parathyrin, and 25(OH)D were measured in all 235 patients. Results. Our results show that patients with T2DM have lower b-CTx values and relatively higher levels of P1NP, reflecting less pronounced changes in bone metabolism compared to patients with T1DM, regardless of age or duration of the disease. Osteoporosis was detected in 50% of patients with T1DM, compared to 13% of patients with T2DM. Conclusion. In some cases, bone remodeling markers are useful for improving the assessment of the state of bone tissue in early stages of diabetes, while alterations in bone microarchitecture may not always be captured by bone mineral density measurements.